Aporia and diaspora: the unliveable life in Dinaw Mengestu's How to Read the Air. Issue 2 (4th May 2018) - Hamilton, Grant
Abstract: This article argues that the first-generation diasporic experience staged in Dinaw Mengestu's recent novel, How to Read the Air, is one of a lived dissonance – of a combat between the experience of a (new) world that the diasporic subject knows nothing about, but a world in which she is nonetheless expected (even by herself) to fully participate. The result of this lived dissonance is a kind of paralysis, a kind of stuttering that arises from the inability to unthinkingly navigate the world. Read through Jacques Derrida's work on aporia, Mengestu's account of diasporic experience is one that presents a life that must be lived even though it is at the same time a life that cannot be lived because everything in the "new world" is inevitably unknown, uncertain, and undecided. In this way, Mengestu writes first-generation diasporic experience as aporia – something one might rephrase as an unliveable life.